Mythbusting The Effect of BCAA on Wound Healing - Ferdian Tanaka; Shaza Nathasya Sandakh; Geovan Hananto; Antonius Setiadi (Jurnal Plastik Rekonstruksi, 2025)
Nutrition plays a crucial role in the wound-healing process. Nutrition deficiencies can hinder the wound healing process and prolong the recovery period turning the wound into a chronic wound. One nutrient that is rarely discussed is BCAA (Branched Chain Amino Acid). BCAA are essential amino acids that are believed to accelerate the wound healing process. This study aims to investigate the effects of BCAA on the wound healing process. Studies have shown that BCAAs can increase serum albumin levels by preventing the formation of mRNA-PTB (Polypyrimidine Tract-Binding Protein) in liver cells, which activates and accelerates the wound healing process. Administering BCAA as a single treatment is not optimal; therefore, combined therapy with other essential amino acids is necessary. BCAAs can be administered orally, enterally, parenterally, and topically.